EFEKTIVITAS PEMBELAJARAN LANGSUNG TERHADAP PENCAPAIAN HASIL BELAJAR KETERAMPILAN PSIKOMOTOR SISWA KELAS VI SDN 021 TELUK KUANTAN - Zulirfan Zulirfan (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2008)
The purpose of this research is to know the effectiveness of physic learning through direct instruction methodin the result of student psychomotor skill achievement. The subject of this research is 29 students of SDN 021Teluk Kuantan in period 2007/2008. The chosen of main subject is Electricity Series. Data is collected bygiving the applicative psychomotor test after finishing the subject. The data of this result is analyzeddescriptively with consists of: student’s achievement and learning completeness. The result analysis showedthe student’s achievement is categorized very good, learning and material completeness of psychomotor skillis categorized complete. So, the direct instruction method is clarified very effective for science psychomotorskill achievement of sixth year students at SDN 021 Teluk Kuantan, in Kuantan Singingi district.Key words: direct instruction, science psychomotor skill.